Crystallographic orientation dependence of deformation-induced martensitic transformation of 1.3 GPa-class 0.6 %C bainitic steel with retained austenite. (15th March 2021) - Ueji, Rintaro; Shibata, Akinobu; Ushioda, Kohsaku; Kimura, Yuuji; Ohmura, Takahito; Inoue, Tadanobu
Abstract: The crystallographic orientation dependence of the stability of retained austenite against deformation-induced martensitic transformation in 0.6 %C alloyed steel was studied. A bainite structure with about 40 % volume fraction of retained austenite was successfully obtained by austempering. Tensile testing at room temperature revealed a high strength of 1.3 GPa with adequate elongation. A change in texture of retained austenite brought about by tensile deformation to several strains was measured. Deformation-induced martensitic transformation occurred preferentially in grains with the tensile axis nearly parallel to <001>fcc . The orientation dependence of the martensitic transformation was compatible with that of the 1-11fcc <121>fcc shear deformation which can be regarded as the first primitive process for the martensitic transformation as proposed by Bogers and Burgers. This compatibility is discussed in terms of the elastically normalized Schmid factor for the transformation dislocation to act for the lattice change. Graphical abstract: Image, graphical abstract